Quality of Life and Some Related Factors in Patients With Beta Thalassemia Major in Southwest Iran - Mostafa Madmoli; Yaghoob Madmoli; Peyman Rahmati; Ahmad Adavi; Najme Yousefi; Zohre Gheisari; Marzie Abbaszade Aliabad (Iran University of Medical Sciences, 2017)
Background: Thalassemia is one of the most common genetic disorders in the world, especially in Iran. The study of various aspects affecting the physical and mental health of patients with beta thalassemia major has become more important. The aim of this study was to evaluate the Quality of life and some related factors in patients with beta-thalassemia major in Southwest Iran. Methods: In this cross-sectional, descriptive study, quality of life and related factors in 112 thalassemia major patients with available sampling attending Dezful Thalassemia Center has been studied in the first three months of 2015. Data collection was based on self-report including demographic questionnaire and 36-SF quality of life questionnaire. Finally, the data were analyzed using SPSS software version 18 and chi-square test, T-test, and Pearson's correlation coefficients. Results: Patients with beta thalassemia major, including 66 males (58.92%) and 46 females (41.07%) with a mean age of 23 years were enrolled in the study. The lowest and highest scores were obtained in general health (63.59) and physical functioning (85.25), respectively. Findings showed that there is no statistically significant difference (P = 0.025) between men and women in all aspects of quality of life except role disorder. It was also found that married people have a higher quality of life and mental health in comparison to other people (P < 0.05). In addition, there was a negative correlation between age and physical health, mental health, and quality of life total scores which were not statistically significant (P = 0.46).  Conclusion: The present study results showed well that age, income level, and marital status indices play a very important role in the maintenance of quality of life and the reduction of negative effects of disease on patient's mental and physical health. The limitations of this study are to examine the dimensions of quality of life in a center. It seems that future studies should look at ways to improve their quality of life.